A second species of Gegeneophis Peters (Amphibia: Gymnophiona: Caeciliidae) lacking secondary annular grooves - Giri, Varad; Gower, David J.; Gaikwad, Kshamata; Wilkinson, Mark (Zootaxa, 2011)
A new species of caecilian amphibian, Gegeneophis pareshi sp. nov., is described based on a series of 16 type specimens from the Western Ghats region of southern Goa, India. This species differs from all other congeners except G. seshachari Ravichandran, Gower & Wilkinson, 2003 in lacking secondary annular grooves and possessing an unsegmented terminal ‘shield’. It differs from G. seshachari in having many more primary annuli and a distinct colour pattern with a largely unpigmented head and pale anterior body.